2019
DOI: 10.1148/radiol.2019181652
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Thermal Accelerant Gel on Microwave Ablation Zone Volumes in Lung: A Porcine Study

Abstract: Background: Thermal ablation of cancers may be associated with high rates of local tumor progression. A thermal accelerant gel has been developed to improve the transmission of microwave energy in biologic tissues with the aim of enlarging the thermal ablation zone. Purpose: To determine the effects of a thermal accelerant gel on microwave ablation zone volumes in porcine lung and to compare percutaneous and endobronchial delivery methods. Materials and Methods: Thirty-two consecutive microwave lung ablations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…TA is considered a safe treatment for primary lung cancer ( 7 , 20 , 21 ). As an alternative therapy to surgical resection, TA causes irreversible damage to tumor cells using thermal energy ( 14 , 31 , 32 ). While previous studies have shown that TA is beneficial for stage I NSCLC patients ( 7 , 18 , 33 ), however, there is minimal data on the use of TA in stage II-III NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TA is considered a safe treatment for primary lung cancer ( 7 , 20 , 21 ). As an alternative therapy to surgical resection, TA causes irreversible damage to tumor cells using thermal energy ( 14 , 31 , 32 ). While previous studies have shown that TA is beneficial for stage I NSCLC patients ( 7 , 18 , 33 ), however, there is minimal data on the use of TA in stage II-III NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…TA includes radiofrequency ablation (RFA), microwave ablation (MWA), and ultrasound ablation using various energy sources ( 12 , 13 ). As a minimally invasive treatment technique, TA utilizes thermal energy to cause injuries to the targeted tissue ( 14 ). Of the ablation technologies in clinical use, RFA is the most widely used for the treatment of multiple conditions, including cardiac arrhythmias and liver, lung, kidney, and other tumors ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Microwave technology was observed to be more efficient than radiofrequency 15 . Currently the thermal effect of microwave application has been enhanced by adding transbronchial thermal gel 16 . Moreover; thermosphere technology combined with microwave ablation has increased the efficiency of the method 13 .…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, ex vivo liver experiments revealed larger ablation zones in the forward direction when compared with prior designs [13] , [14] . Another experimental approach is the use of thermal accelerants that are designed to augment microwave energy transmission, resulting in faster heating and larger ablation volumes [15] , [16] . In a study by Maxwell et al, the use of thermal accelerants was associated with an average 40% increase in ablation volumes compared to standard ablations in in vivo swine (22.2 cm 3 vs 15.9 cm 3 ) as well as producing more spherical ablation volumes [17] .…”
Section: Introductionmentioning
confidence: 99%